TINJAUAN LITERATUR: IMPLEMENTASI PENGGUNAAN E-MONEY SEBAGAI PENDUKUNG CASHLESS SOCIETY DI INDONESIA - Jagaddhita, I Kadek Ekna Satria; Kusuma, Putu Sri Arta Jaya (ITB Swadharma, 2024)
This research aims to investigate the use of electronic money (e-money) as a catalyst for the advancement of the cashless society concept in Indonesia. In today's digital landscape, society is compelled to harness technology across various spheres of life, particularly in financial transactions. The adoption of e-money, a constituent of financial technology (fintech), is steadily proliferating, spanning from online shopping transactions and public transportation fares to regular bill settlements. Employing a literature review methodology, this research entails gathering and evaluating literature pertinent to the evolution of e-money technology, governmental regulations, benefits, and challenges encountered in fostering the realization of a cashless society in Indonesia. Findings suggest that the implementation of e-money holds significant promise in supporting the materialization of a cashless society in Indonesia. The utilization of e-money yields substantial positive impacts on the financial performance of Small and Medium Enterprises (SMEs) and has the potential to enhance financial inclusivity. However, several obstacles such as data security, privacy concerns, and the populace's limited digital literacy pose challenges. Therefore, addressing these hurdles through enhanced digital literacy initiatives and fortified security protocols is imperative to attain a more comprehensive and efficient cashless society.Tujuan dari penelitian ini untuk menyelidiki penerapan penggunaan uang elektronik (e-money) sebagai bagian dari upaya masyarakat menuju cashless society di Indonesia. Di era digital ini, masyarakat dihadapkan pada kebutuhan untuk memanfaatkan teknologi dalam berbagai aspek kehidupan, termasuk transaksi keuangan. Penggunaan e-money sebagai bagian dari teknologi keuangan (fintech) semakin meluas, mencakup pembayaran belanja daring, transportasi umum, hingga pembayaran tagihan rutin. Metode penelitian yang diterapkan adalah tinjauan pustaka, yang mencakup pengumpulan dan evaluasi berbagai literatur yang relevan dengan perkembangan teknologi e-money, kebijakan pemerintah, manfaat, serta hambatan dalam mewujudkan cashless society di Indonesia. Temuan dari penelitian menunjukkan bahwa implementasi e-money memiliki potensi besar dalam mendukung pencapaian cashless society di Indonesia, dengan dampak positif yang signifikan terhadap kinerja keuangan UMKM dan peningkatan inklusi keuangan. Meski demikian, terdapat sejumlah tantangan seperti masalah keamanan data, privasi, dan rendahnya literasi digital di kalangan masyarakat. Oleh karena itu, untuk mencapai cashless society yang lebih inklusif dan efisien, tantangan-tantangan ini harus diatasi melalui upaya peningkatan literasi digital dan penguatan regulasi keamanan.